2023
DOI: 10.1021/acs.jafc.2c08710
|View full text |Cite
|
Sign up to set email alerts
|

Ethylidene-Tethered Chromene–Pyrone Hybrids as Potential Plant-Growth Regulators from an Endolichenic Phaeosphaeria Species

Abstract: Phaeosphaeria sp., a lichen-associated fungus, produced six skeletally new dimeric spiciferones (1–6) and four known metabolites (7–10). The new structures were elucidated by spectroscopic analysis, and their absolute configurations were determined by electronic circular dichroism calculations. Compounds 1 and 3–6 represent the first examples of ethylidene-bridged dimers from the building blocks 4H-chromene-4,7(8H)-dione and α-pyrone, and 2 is a unique homodimer of spiciferone. Compounds 1, 2, and 5–9 signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A metabolite produced by Phaeosphaeria sp., a fungus related to lichens, was found in the leaves. Yi–Jie Zhai et al found that its metabolites 1 and 8 promoted the growth of rice stem and root elongation in a dose-dependent manner [ 17 ]. Many studies have shown that Kondoa is a yeast isolated from leaves and soil [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A metabolite produced by Phaeosphaeria sp., a fungus related to lichens, was found in the leaves. Yi–Jie Zhai et al found that its metabolites 1 and 8 promoted the growth of rice stem and root elongation in a dose-dependent manner [ 17 ]. Many studies have shown that Kondoa is a yeast isolated from leaves and soil [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…. Fungi 2024, 10, x FOR PEER REVIEW 9 of 49 (64), 6,8-dihydroxy-4-hydroxymethyl-3,5-dimethyl-isochro-men-1-one (65), decarboxyhy droxycitrinone (66), acremonone G (67), O-methylmellein (68), and trans-4-hydroxymel lein (69), were isolated by Wang et al from the endolichenic fungus Apiospora montagne [23]. Among them, compound 67 exhibited significant cytotoxicity against the L5178 mu rine lymphoma cell line, with an IC50 value of 2.7 µM.…”
Section: Simple Aromatic Polyketidesmentioning
confidence: 99%
“…The terphenyl deriva- In 2023, six spiciferone-derived dimers with an unprecedented skeleton, named phaeosphaerones A-F (251-256), were reported and isolated from the endolichenic fungus Phaeosphaeria sp. [64], and most of them were composed of a novel 4H-chromene-4,7(8H)dione scaffold and an α-pyrone unit, forming fascinating dimeric compounds. Among them, compounds 251 and 253-256 possessed unconventional carbon skeletons featuring an ethylidene bridge, whereas compound 252 was a structurally interesting homodimer of spiciferone, which might be furnished by an unusual Rauhut-Currier reaction.…”
Section: Polyphenylsmentioning
confidence: 99%
“…19 However, endophytic fungi associated with Pedicularis sylvatica L. have rarely been investigated. In continuing research into endophytic fungi, [20][21][22] a fungus associated with Pedicularis sylvatica produced four undescribed metabolites, aspeversins A-D (1, 2, 5 and 6), and four known compounds (3, 4, 7 and 8) (Fig. 1), which showed α-glucosidase inhibitory and neuroprotective activities.…”
Section: Introductionmentioning
confidence: 99%